Quantitative analysis of the velocity and synchronicity of diaphragmatic motion: dynamic MRI in different postures - Kiryu, Shigeru; Loring, Stephen H.; Mori, Yasutane; Rofsky, Neil M.; Hatabu, Hiroto; Takahashi, Masaya (Magnetic resonance imaging, 2006)
The objectives of this study were to assess the relationship between right and left hemidiaphragmatic motions during breathing in normal subjects and to investigate alterations in lung motion with changes in posture, using dynamic magnetic resonance (MR) imaging. Imaging was conducted with a 1.5-T MR scanner using fast imaging employing steady-state acquisition with a torso coil. Eight healthy subjects were instructed to breathe from end-inspiration to end-expiration as slowly and as deeply as possible. Imaging and breathing were started together to afford sequential images on the coronal plane. Imaging sequences were performed in supine, prone, left lateral decubitus and right lateral decubitus postures. The component of movement of the most cephalic point in the cephalocaudal axis was measured, and the diaphragmatic excursion (maximum hemidiaphragmatic displacement), synchrony and velocity of the right and left hemidiaphragmatic motions were calculated during the expiratory phase and the inspiratory phase, respectively. Excursion was greater in the right hemidiaphragm in most postures, except the left lateral decubitus. In supine and prone postures, both hemidiaphragms moved synchronously in both inspiratory and expiratory phases. In both lateral decubitus postures, the hemidiaphragms moved asynchronously with different velocities in the expiratory phase but with the same velocities in the inspiratory phase. The method described here allowed the assessment of diaphragmatic motions. Motions in the right and left hemidiaphragms changed with posture. In addition, diaphragmatic motion differed between expiratory and inspiratory phases. This study suggests the further potential of dynamic MR imaging for the evaluation of pulmonary functions or deficiencies.